Analisis Strategi Sukses Model Bisnis Startup E-Commerce di Era Digital Menggunakan Metode Value Proposition Design - Risky Amelia; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the digital age, e-commerce startups are racing to achieve success. However, behind sophisticated technology, the key to success lies in understanding and meeting customer needs. Value Proposition Design (VPD) emerges as an effective strategy for designing customer-centric business models. This study aims to examine the role of VPD in building successful e-commerce startup business models in the digital era. Using a qualitative approach and case studies, this research analyzes the experiences and strategies of several successful e-commerce startups in Indonesia that have implemented VPD. The findings indicate that VPD helps startups identify customer needs, design relevant value propositions, and build sustainable competitive advantages. Moreover, the study reveals the challenges and opportunities faced in implementing VPD in a constantly evolving environment. In conclusion, VPD is a crucial strategy that can enhance the competitiveness of e-commerce startups in the digital age. This research provides recommendations for entrepreneurs to understand and consistently implement VPD.